Karakteristik Isolator Komposit Berbasis Biomassa: Literatur Review (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The increasing need for insulation in electric power systems encourages the discovery of high-performance and sustainable dielectric materials. This study presents a Literature Review of biomass-based composite insulator research from 2018-2025 to synthesize the effect of filler type and treatment on the electrical, thermal, and mechanical properties of polymer composites. Literature was analyzed from reputable databases with inclusion criteria, and thematic analysis data extraction. Processing methods generally include washing, acid/alkali treatment, calcination, and advanced production techniques such as sol-gel and ultrasonication, integration of biomass fillers especially at low fractions (3-7%). The results show 1) the dominance of the use of rice husk as a source of biosilica for the main matrix filler of the insulator. 2) the performance of biomass composite insulators is highly dependent on the quality of purification, particle size, and surface modification of the filler. 3) there is a significant increase in the insulator's breakdown strength, resistivity, and thermal stability with the addition of biomass fillers to the main matrix. 4) the long-term stability of biomass materials against humidity and thermal aging has not been evaluated in depth.